School Related Gender Based Violence Among Female Undergraduates - Odigie, Eunice; Aideyan, Daniel Osarenmwanta (Universitas Mercu Buana Yogyakarta, 2024)
This study investigated the school-related gender-based violence among female undergraduates. Three research questions and two hypotheses were raised to guide the research. Literatures related to the studies were reviewed. The study adopted the descriptive survey research design and the population of the study comprised twenty-one thousand, eight hundred and fifty-two full-time undergraduate students in University of Benin. The multi-staged sampling technique was used to select 235 respondents for the study. A Self-structured questionnaire was used for the collection of data. The research instrument was content validated and a reliability coefficient of 0.82 was obtained using the test-retest reliability method. Data obtained were analysed using inferential statistics of t-test and descriptive Statistics of frequency counts and percentages and chart. Some of the findings revealed that majority of the respondents have experienced various types of school related gender-based violence that does not differ by age. With reference to the findings, the researchers recommended among others that school management should develop and implement comprehensive awareness initiatives aimed at educating students and school personnel on recognizing, preventing, and addressing school-related gender-based violence. Keywords: School-related, gender-based violence, undergraduates, predictive factors.